Impact of Modified Atmospheres on Growth and Metabolism of Meat-Spoilage Relevant Photobacterium spp. as Predicted by Comparative Proteomics - Fuertes-Perez, Sandra; Abele, Miriam; Ludwig, Christina; Vogel, Rudi F.; Hilgarth, Maik (Frontiers in Microbiology, 2022)
Modified atmosphere packaging (MAP) is a common strategy to selectively prevent the growth of certain species of meat spoiling bacteria. This study aimed to determine the impact of high oxygen MAP (70% O2, 30% CO2, red and white meats) and oxygen-free MAP (70% N2, 30% CO2, also white meat and seafood) on preventing the growth of spoiling photobacteria on meat. Growth of Photobacterium carnosum and P. phosphoreum was monitored in a meat simulation media under different gas mixtures of nitrogen, oxygen, and carbon dioxide, and samples were taken during exponential growth for a comparative proteomic analysis. Growth under air atmosphere appears optimal, particularly for P. carnosum. Enhanced protein accumulation affected energy metabolism, respiration, oxygen consuming reactions, and lipid usage. However, all the other atmospheres show some degree of growth reduction. An increase in oxygen concentration leads to an increase in enzymes counteracting oxidative stress for both species and enhancement of heme utilization and iron-sulfur cluster assembly proteins for P. phosphoreum. Absence of oxygen appears to switch the metabolism toward fermentative pathways where either ribose (P. phosphoreum) or glycogen (P. carnosum) appear to be the preferred substrates. Additionally, it promotes the use of alternative electron donors/acceptors, mainly formate and nitrate/nitrite. Stress response is manifested as an enhanced accumulation of enzymes that is able to produce ammonia (e.g., carbonic anhydrase, hydroxylamine reductase) and regulate osmotic stress. Our results suggest that photobacteria do not sense the environmental levels of carbon dioxide, but rather adapt to their own anaerobic metabolism. The regulation in presence of carbon dioxide is limited and strain-specific under anaerobic conditions. However, when oxygen at air-like concentration (21%) is present together with carbon dioxide (30%), the oxidative stress appears enhanced compared to air conditions (very low carbon dioxide), as explained if both gases have a synergistic effect. This is further supported by the increase in oxygen concentration in the presence of carbon dioxide. The atmosphere is able to fully inhibit P. carnosum, heavily reduce P. phosphoreum growth in vitro, and trigger diversification of energy production with higher energetic cost, highlighting the importance of concomitant bacteria for their growth on raw meat under said atmosphere.